Antimicrobial Activity of Goat Colostrum Against Bacterial Strains Causing Food Poisoning Diseases - Setyawardani, Triana; Sumarmono, Juni; Risqiati, Heni; Santosa, Setya Agus (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
The study was aimed to investigate the antimicrobial activity of bacterial isolates L.plantarum 3CT7 and 20CT8 from goat colostrum. The antimicrobial activity of cell-free supernatant was tested using a well-diffusion method on several indicators: temperature, time of storage, and pH. Antimicrobial activity was recorded in both isolates at pH 2.0; 4.0; 6.0 and 8.0, temperature at 0, 50 and 100 oC, and in cold storage for 0, 15, 30, 45 and 60 days. L.plantarum 7CT3 and L.plantarum 20CT8Â have a bigger zone of inhibition than that of Pseudomonas spp. as compared to other bacteria. Testing the cell-free activity was aimed to investigate the metabolite inhibition by L.plantarum. The isolates were capable of inhibiting all pathogenic bacteria in the experiment (S. thypimurium, E. coli, and S. aureus)Â as evidenced from the similar zone of inhibition from 15.83 to 16.06 mm. Isolates (L. plantarum 7CT3 dan 20CT8) exhibit inhibitory properties against S.thypimurium, S. aureus, Pseudomonas spp.. and L. monocytogenes at 0, 50 and 100oC. L.plantarum 7CT3 and L.plantarum 20CT8 exhibit antimicrobial activity during cold storage. Both isolates grown in the range of pH from 2 to 8 could inhibit S. thypimurium, E. coli, S. aureus and Pseudomonas spp.Â In general, the two isolates are the potential antimicrobial activity with broad ranges of pH, temperature and storage time.